A Botanist's guide to rituals and revenge - Khavari, Kate; Khavari, Kate (Khavari, Kate. Saffron Everleigh mystery, 2025)
"Returning to Ellington Manor, Saffron Everleigh faces tense family relationships made worse by enigmatic Bill Wyatt, hired as doctor to the ailing Lord Easting, but who in reality is involved in trafficking dangerous government secrets-and whose presence can only mean trouble"--